2017
DOI: 10.5539/ijef.v9n5p44
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IFRS on Accounting Information Quality: Evidence for Brazil

Abstract: Understanding the effects of the International Financial Reporting Standards (IFRS) on accounting quality is fundamental for policy makers and financial market players in general. This paper analyzes whether the adoption of IFRS in Brazil has had the impact on accounting informational quality. To this end, a differentiated empirical strategy was adopted based on two steps: first, a matching of voluntary adopters of norms and non-adopters by propensity score is performed to construct control groups. This is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Several studies have discussed the characteristics of accounting information such as Beest et al (2009), Jing and Harbin: School Of Management, Harbin Institute Of Technology, P.R.China. (2007), Obaidat (2007), Kallob and Buhaisi (2013), Kythreotis (2014), Tsoncheva (2014), Yurisandi and Puspitasari (2015), Junior et al (2017), Nobes and Stadler (2015), Mbobo and Ekpo (2016), AL-Shatnawi (2017), Al-dmour et al (2017), Mbawuni (2019. Jonas and Blanchet (2000) developed a generally acceptable framework between management, auditors and audit committees to assess the quality of inancial reports.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have discussed the characteristics of accounting information such as Beest et al (2009), Jing and Harbin: School Of Management, Harbin Institute Of Technology, P.R.China. (2007), Obaidat (2007), Kallob and Buhaisi (2013), Kythreotis (2014), Tsoncheva (2014), Yurisandi and Puspitasari (2015), Junior et al (2017), Nobes and Stadler (2015), Mbobo and Ekpo (2016), AL-Shatnawi (2017), Al-dmour et al (2017), Mbawuni (2019. Jonas and Blanchet (2000) developed a generally acceptable framework between management, auditors and audit committees to assess the quality of inancial reports.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Similarly, Junior et al (2017) analyzed whether the adoption of IFRS has had an effect on the accounting information quality in brazil, the results revealed a positive impact of IFRS on the value relevance; and not found suf icient evidence toward timelines and conservatism Nobes and Stadler (2015) investigated the use of qualitative characteristics by company managers to assist them in making decisions by using publicly available data. The study found that comparability was more used, especially comparison regarding the type of industry, then that relevance, faithful representation, and understandability were important.…”
Section: Review Of Literaturementioning
confidence: 99%